2010
DOI: 10.1108/09590551011062457
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of detergent‐retail brands: the role of consumer confidence and trust

Abstract: Purpose -The aim of this paper is to analyse the role of "trust" and "confidence/pessimism" in influencing consumer attitudes and buying intentions with respect to retail brands and products. Design/methodology/approach -Following a review of the relevant literature, the paper presents a conceptual model of buying intentions regarding retail brands. The model is then tested quantitatively by structural equation modelling analysis using a sample of 581 adult consumers that are decision makers in their household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 57 publications
2
35
0
1
Order By: Relevance
“…These factors are low price and high perceived quality (Burton et al 1998;Sinha, Batra 1999;Zielke, Dobbelstein 2007;Baltas, Argouslidis 2007;Anchor, Kourilova 2009). The research has further confirmed that the propensity to purchase own brands is greatly influenced by the relationship between price and quality (Gomez, Fernandez 2009;Lymperopoulos et al 2010), and the main driver of own brand acceptance is its relatively low price and the improved quality (Cooper, Nelson 2003;Lymperopoulos et al 2010). …”
Section: From Product Perspectivesupporting
confidence: 59%
See 1 more Smart Citation
“…These factors are low price and high perceived quality (Burton et al 1998;Sinha, Batra 1999;Zielke, Dobbelstein 2007;Baltas, Argouslidis 2007;Anchor, Kourilova 2009). The research has further confirmed that the propensity to purchase own brands is greatly influenced by the relationship between price and quality (Gomez, Fernandez 2009;Lymperopoulos et al 2010), and the main driver of own brand acceptance is its relatively low price and the improved quality (Cooper, Nelson 2003;Lymperopoulos et al 2010). …”
Section: From Product Perspectivesupporting
confidence: 59%
“…There are various terms for own brands: own label, private label, house brand, retailer brand, and exclusive brand, store brand, etc., (DelVecchio 2001;Veloutsou et al 2004;Lymperopoulos et al 2010). These terms have been used by retailers and researchers interchangeably even though scholars such as McGoldrick believe these terms are different (2002).…”
Section: Introductionmentioning
confidence: 97%
“…This last consideration could be also the consequence of the relevant selling results registered by this alternative value proposition or its developing differentiation, above all when there is a structured retail distribution system (Cuneo et al, 2015). PLs presence is surely not a novelty but, the continuous increasing market share is an important feature to observe (Calvo Porral, & Levy-Mangin, 2016), evaluating the strategic role in the competition among retailers (Lymperopoulos et al, 2010). PLs appeared in the market from the first decades of the last century, specifically from the 1930' in the U.S. context, thanks to the work of the major chain retailers, as noted by Call (1967).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, distrust is a useful mental state that enables us to get rid of systems or individuals and organizations that are unreliable and unhealthy (4). Another definition of trust in this way is the psychological state consisting of the acceptance of the vulnerability based on the behavior of the positive expectations of the other (5). Brand trust is the degree of brand ability and capacity to meet promises made.…”
Section: Introductionmentioning
confidence: 99%